Active tectonics and kinematics of Fethiye-Göcek Bay, SW Turkey: Insight about the eastern edge of Pliny-Strabo Trenches. (April 2021) - Tosun, Levent; Avşar, Ulaş; Avşar, Özgür; Dondurur, Derman; Kaymakcı, Nuretdin
Abstract: Pliny-Strabo Trench (PST)is a Subduction Transform Edge Propagator (STEP) fault developed at the northern edge of the African oceanic lithosphere connecting the Aegean and Cyprian trenches in the eastern Mediterranean. Recent studies have demonstrated that the PST terminates close to Turkish Border and links to the Cyprian trench east of Rhodes and south of Fethiye-Göcek Bay. However, it is also claimed that the PST extends into SW Anatolia along a sinistral transtensional shear zone, so-called Fethiye-Burdur Fault Zone (FBFZ) implying that a lithospheric tear in the downgoing plate extends into the over-riding plate, although, this is kinematically almost impossible since full mechanical coupling between down going and the over-riding plate is necessary. To test this hypothesis and understand the kinematics of the transition zone between PST and Cyprian trench we have conducted a rigorous paleostress inversion study combined with interpretation of 2D seismic data of which 228 km total length obtained from Fethiye-Göcek Bay. The seismic reflection data are used for the interpretation and delineation of off-shore faults and to determine their recent activity. The geometry and kinematics of the exposed on-land faults are determined by analyzing 13969 fault slip data obtained from 211 sites distributed evenly throughout in an area encompassing the bay in an area extending 70 km in E-W and 50 km in N–S that cover the whole area where the Pliny-Strabo STEP fault would emerge on-land. Results of analyses indicated that most of the faults in the study area are developed under multi-directional extension, except for some NE-SW-striking faults, which have dextral strike-slip components contrary to proposed sinistral nature of Fethiye-Burdur Fault Zone. Although there are numerous normal faults some which have been active until recently, however, there is almost no NE-SW striking sinistral strike-slip fault in the region to justify the presence of Fethiye-Burdur Shear Zone. Additionally, there are a number of earthquakes with dominantly strike-slip moment tensor solutions in the deeper part of the bay while they are in normal character in the on-shore areas suggesting that the Pliny-Strabo Trench stops very close to the shoreline and it does not propagate into SW Anatolia. Therefore, existence and alleged characteristics of the Fethiye-Burdur Fault Zone could not be verified. Graphical abstract: Image 1 Highlights: Fethiye-Göcek Bay area is dominated by normal faults developed under multidirectional extensional deformation. The offshore strike-slip faults related to Pliny-Strabo Trenches do not extend NE into the on-shore SW Anatolia. There is no evidence supporting any NE-SW striking major strike-slip fault around Göcek-Fethiye Bay. Existence and previously proposed kinematics of Fethiye-Burdur Fault/Shear Zone is not validated.